2018
DOI: 10.1002/smll.201703683
|View full text |Cite
|
Sign up to set email alerts
|

Smart‐Dust‐Nanorice for Enhancement of Endogenous Raman Signal, Contrast in Photoacoustic Imaging, and T2‐Shortening in Magnetic Resonance Imaging

Abstract: Raman microspectroscopy provides chemo-selective image contrast, sub-micrometer resolution, and multiplexing capabilities. However, it suffers from weak signals resulting in image-acquisition times of up to several hours. Surface-enhanced Raman scattering (SERS) can dramatically enhance signals of molecules in close vicinity of metallic surfaces and overcome this limitation. Multimodal, SERS-active nanoparticles are usually labeled with Raman marker molecules, limiting SERS to the coating material. In order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Exogenous contrast agents, such as organic dyes [60][61][62], genetically encoded proteins [63][64][65][66], and micro/nanoparticles [67][68][69][70][71], have been extensively explored for PA molecular imaging. With the innovations and advances in exogenous contrast agents, molecular PAT has recently enjoyed a prosperous development (Figure 4).…”
Section: Molecular Pactmentioning
confidence: 99%
“…Exogenous contrast agents, such as organic dyes [60][61][62], genetically encoded proteins [63][64][65][66], and micro/nanoparticles [67][68][69][70][71], have been extensively explored for PA molecular imaging. With the innovations and advances in exogenous contrast agents, molecular PAT has recently enjoyed a prosperous development (Figure 4).…”
Section: Molecular Pactmentioning
confidence: 99%
“…Core–shell AuNR have also been developed that are effective contrast agents for multiple modalities . Notably, a spindle-shaped iron oxide core that offers T 2 contrast in MRI was covered in a gold shell to yield a probe referred to as “nanorice”, that allowed multimodal imaging by MRI, PAI in the NIR and SERS . Other original shape variations have been developed to fine-tune both the optical properties and the cellular uptake of AuNP, such as prisms, stars, and triangles .…”
Section: Introductionmentioning
confidence: 99%
“…36 Notably, a spindle-shaped iron oxide core that offers T 2 contrast in MRI was covered in a gold shell to yield a probe referred to as "nanorice", that allowed multimodal imaging by MRI, PAI in the NIR and SERS. 37 Other original shape variations have been developed to fine-tune both the optical properties and the cellular uptake of AuNP, such as prisms, stars, and triangles. 38 The strong light scattering properties of gold nanoprisms make them valuable contrast agents for imaging the microvasculature in skin or in melanoma tumors using OCT. 39 Stars provide a high surfaceto-core ratio which is advantageous for surface functionalization with targeting ligands, and allow molecular imaging with SERS 40,41 or CT. 42 Furthermore, the effect of the shape of AuNP on their accumulation in RAW264.7 macrophages was evaluated comparing stars, prisms, and triangles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Gold-manganese dioxide nanoparticles have shown potential for improving the effectiveness of cancer diagnosis and treatment through multimodal imaging. [188][189][190] One study shows the result of the combination of photoacoustic and MRI imaging for more accurate diagnosis. [191][192][193][194] Wang et al 195 demonstrated that gold-manganese dioxide core-shell nanostructures could be used for dual photoacoustic and MR imaging, showing high stability under physiological conditions (Fig.…”
Section: Mno 2 For Photoacoustic Imagingmentioning
confidence: 99%